Low grade serous ovarian carcinoma presenting with monoparesis due to deep vein thrombosis: a case report - Bhadra, Avishek; Dey, Ramprasad; Biswas, Rumela; Bagchi, Subhojit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Low-grade serous ovarian carcinoma (LGSOC) is a rare and indolent form of ovarian cancer. While it commonly presents with abdominal symptoms, unusual manifestations such as neurological deficits are less frequent. This case report explores an atypical presentation of LGSOC associated with deep vein thrombosis (DVT) leading to monoparesis. A 45-year-old multiparous female, regular menstrual cycles presented with sudden onset of swelling and pain in her left lower limb. Physical examination revealed tender and swollen left lower limb with Homan’s sign, with imaging confirming DVT in multiple lower limb veins. Further investigation, including pelvic imaging, revealed an ovarian mass. DVT was managed conservatively and patient had total abdominal hysterectomy with bilateral salpingo oophorectomy. Biopsy revealed LGSOC with external iliac vein thrombosis. The tumor was initially asymptomatic, and the neurological symptoms were attributed to paraneoplastic syndrome secondary to the DVT rather than direct tumor invasion. This case highlights an atypical presentation of LGSOC where DVT complicated by monoparesis was the primary symptom. It underscores the importance of considering underlying malignancies in patients with unexplained neurological symptoms and venous thromboembolism (VTE). Early recognition and comprehensive evaluation are crucial for appropriate diagnosis and management. LGSOC can present with unusual neurological symptoms, particularly when complicated by DVT. Clinicians should be vigilant for potential malignancies in patients with unexplained monoparesis and thromboembolic events to ensure timely and effective treatment.